Integration of climate-smart agriculture interventions to the agriculture sector development plan - Malihan, Maria Angela A.; Liwag, Carmelita R.E.U. (Quezon City School of Urban and Regional Planning, University of the Philippines Diliman, 2018)
Rice remains an important crop as food and as a source of livelihood in the Philippines (Department of Agriculture [DA] 2012). Recently, the country experienced rice shortages due to several factors, which include climate change. The rice plant is considered as the most vulnerable crop to the changing climate (Mohanty et al. 2013). However, rice production is one of the major contributors of greenhouse gas (GHG) emissions that aggravate climate change. In the Philippines, the agriculture sector is the second largest GHG emission source (26% of the total emission), with rice cultivation as the top contributor (63% of the total agricultural emissions)(Dikitanan et al. 2017). Due to these interconnected problems of food productivity, climate change adaptation, and mitigation, the Food and Agriculture Organization (FAO) introduced the concept of Climate-Smart Agriculture (CSA). CSA is an approach that intends to transform and reorient agricultural development under the new realities of climate change (Lipper et al.2014). The aims of this thesis were two-fold. First, to determine the integration and implementation process of CSA in agriculture sector of Guinayangan, Quezon. Second, to develop CSA strategies for rice that other local government units (LGUs) in the Philippines can adopt based on the experiences of Guinayangan. The study employed a combination of quantitative and qualitative research designs to get an in-depth knowledge of the CSA program being implemented at the municipality-level. The study covered the municipality of Guinayangan, Quezon province, one of the pilot sites for the DA's program on Strengthening Implementation of Adaptation and Mitigation Initiative in Agriculture (AMIA) and is a model for CSA. The CSA program in Guinayangan is being jointly implemented by the LGU's Office of the Municipal Agriculture (OMA) and an NGO, the International Institute of Rice Reconstruction (IIRR). Through a community survey, 76 rice farmers from 8 barangays of Guinayangan, Quezon were interviewed. The survey results showed that all of the rice farmer-respondents are already adopting CSA interventions. The top five CSA interventions adopted are (1) enhanced farmers' field school (100%); (2) diversified rice farming system (91%); (3) simple seed banking (72%); (4) water submergence-tolerant varieties (53%); and (5) drought-tolerant varieties (53%). When asked about their perceived benefits on the over-all CSA program, 63 (82%) of the 76 respondents answered that they have benefitted from the CSA program. The most answered benefit is less input but improved rice yield. Looking at the CSA interventions adopted as well as the perceived benefits, one can deduce that the respondents placed higher value on productivity and adaptation, than mitigation. The study also looked into the integration and implementation process of CSA in Guinayangan, Quezon. Based on the key informant interviews, Guinayangan's CSA program is being implemented through this series of activities: (1) situation analysis; (2) prioritization of CSA interventions; (3) program design and implementation; (4) monitoring, evaluation, and learning; and (5) knowledge sharing outside the farmers' learning group. The study also proposed that moving forward, implementers of CSA program for rice could consider climate change hazards, existing farming practices, and the concept of integrated rice management in developing CSA best-bets portfolio for rice to achieve the optimum benefits of CSA (productivity, climate change adaptation, and mitigation).
Thesis (M.A. Urban and Regional Planning)--University of the Philippines Diliman
Keywords: Agriculture; Agriculture -- Economic aspects; Agriculture -- Environmental aspects